2011
DOI: 10.1007/s00268-011-0956-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Sentinel Lymph Node Biopsy Programs in Developing Countries: Challenges and Opportunities

Abstract: It is hoped that this article will be a useful resource for our colleagues planning to establish a SLNB program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…The development of intraoperative optical imaging (31) will enable wider dissemination of SLN mapping to hospitals without access to radiopharmaceuticals. This is especially true in developing countries, where only urban hospitals are equipped to handle radioactivity (32).…”
Section: Molecular Imaging: Sentinel Lymph Node Imagingmentioning
confidence: 99%
“…The development of intraoperative optical imaging (31) will enable wider dissemination of SLN mapping to hospitals without access to radiopharmaceuticals. This is especially true in developing countries, where only urban hospitals are equipped to handle radioactivity (32).…”
Section: Molecular Imaging: Sentinel Lymph Node Imagingmentioning
confidence: 99%
“…Although, it has been stressed that FN rate to be less than 5% for omitting ALND in node-negative cases (Clarke et al, 2004;Lyman et al, 2005;Somasundaram et al, 2009) but most trials haven't achieved FN rate lower than 5% even in Milan trial with very experienced and expert pathologists and about 60 sections per node (Veronesi et al, 2003). So, threshold of 10% (Keshtgar et al, 2011) seems to be a suitable cut-off point for FN rate of SLNB.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Patient 4, only focal involvement of the lymph node was found. In other tumors, such as breast cancer and cutaneous melanoma, it has been found that foci of cancer may be detected microscopically in small, nonpalpable sentinel nodes [7]. Excisional biopsy of a lymph node, even if small, is preferable to fine-needle aspiration in cases such as ours, where study of overall tissue architecture is usually essential for diagnosis.…”
Section: Patientmentioning
confidence: 93%
“…The protein C pathway is a modulator of the coagulation system, and PC itself plays an integral role in the host response to infection, immune system, and cancer cells [1,2]. The extent of PC deficiency assessed at the time of diagnosis has been found to correlate with increased morbidity and mortality [6,7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation